Toward healthy urban streets: Diversity of roadside tree species in industrial area of Shah Alam, Selangor, Malaysia - HASYA HANNANI RUZIMAN; ASMIDA ISMAIL; AZIAN MOHTI; KHAIRUL ADZFA RADZUN; FAEZAH PARDI (Society for Indonesian Biodiversity, 2023)
Abstract. Ruziman HH, Ismail A, Mohti A, Radzun KA, Pardi F. 2023. Toward healthy urban streets: Diversity of roadside tree species in industrial area of Shah Alam, Selangor, Malaysia. Biodiversitas 24: 2674-2681. Shah Alam, one of the biggest cities in Selangor has undergone a significant transformation with numerous developments to cater the needs of the ever-growing population. However, the rapid urbanization and massive infrastructure developments have indirect effects on landscape patterns and roadside tree diversity. Hence, this study was conducted to assess the species richness and diversity of roadside trees in Shah Alam, Selangor. All trees with height of 1 meter and above in Section 15 and 16 were measured and identified as referred to the Landscape Department of Shah Alam City Council (MBSA) computerized database. The data were analyzed for their taxonomic composition and species diversity. A total of 5,523 trees were recorded where 4,087 trees occurred in Section 15 and 1,426 trees in Section 16. Fabaceae was the most dominant family in both sections in which three leading species, i.e. Peltophorum pterocarpum (DC.) Backer ex K.Heyne, Pterocarpus indicus Willd. and Roystonea regia (Kunth) O.F.Cook, accounted for 14.7% of the planted trees. Section 15 was relatively higher in taxonomic composition with 11 families and 25 species than Section 16, with 8 families and 18 species. The values for species diversity index were considered high in both sections with 8.37 despite the environmental impact from the industrial activities. Thus, it is suggested that future research should include the potential risks of biodiversity loss for proper management practices in urban settings.